Strategi Efektif Penggunaan Dana Hibah dalam Perspektif Ekonomi Islam - Alda Julianti; Lena Hirmawati; Herlina Yustati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Grant funds are a potential financial instrument in supporting social, educational, and religious development. In the perspective of Islamic economics, grant fund management has a spiritual dimension that emphasizes sincerity, sustainability, and broad benefits for the community. This study aims to identify effective strategies in managing grant funds in accordance with sharia principles. The research method uses a qualitative approach through literature analysis. The results of the study indicate that the principles of transparency, efficiency, productive empowerment, and sharia supervision are key factors for success in managing grant funds. This strategy not only has a significant impact on beneficiaries, but also strengthens public trust in grant fund management institutions.